Feeding Behavior of Juvenile Oriental Prawn Macrobrachium nipponense Under Laboratory Conditions - Al-Maliky, Tariq H. Y.; Ali, Malik H.; Hashim, Imina A. (Iraqi Journal of Aquaculture, 2021)
The feeding behavior experiment showed that the juveniles of Macrobrachium nipponense mostly and frequently occurred on the artificial net covered wall of the experimental tanks and in all other result feeding of juvenile Macrobrachium nipponense was pelagic and benthic during 2 and 24 hour, in three parts of pond (net wall- A, water column- B and bottom-C) on bottom of ponds smooth and sand-clay, also feeding on pallet. Also showed near of found ratio was 80%, 9%, 11% and 73%, 12%, 14% during 2 hour in parts of pond of smooth and sand-clay respectively, but during 24 hour 72%, 12%, 16% and 67%, 12%, 21% in parts of pond of smooth and sand-clay respectively.